THE EFFECT OF INDUCTOR RESISTANCE ON DEFIBRILLATION ENERGY FROM ELECTROCARDIOGRAPH ENDURANCE TEST SYSTEM - Irawan Sukma; Siddiq Wahyu Hidayat; Wuwus Ardiatna (Widyariset, 2017)
Electrocardiograph endurance test system has two work processes like defibrillator. Charging process produces energy stored in capacitor (ES) and discharges process produce defibrillation energy. Defibrillation energy without connect to electrocardiograph (E2) at test system is influenced by the resistance values of inductor (RL). In previous research, test system only produces E2 = 19,83 joule, this is caused by the inductor used with value RL = 72 Ω. The purpose of this research is to select inductor resistance value to get good and efficient value E2. Range value RLused in test system was 1–10 Ω, based on standar International Electrotechnical Commission (IEC) 60601-2-27 clause 201.8.5.5.2. Voltage measured in point 100 Ω every time interval (∆t) 0,02 ms obtained from multisim software simulation. The result of simulation indicated if peak voltage increased, then value RL was used approach zero. In other side, measured Voltage data was used as parameter to calculate total E2in every range of RLvalue, then result E2total was compared to ES value to get energy ratio value. Value RL= 1 Ω was the most efficient because has ratio energy value 98,45% with E2 = 393,80 joule, while energy ratio when RL= 10 Ω was not efficient because only had energy ratio value 89,58% with E2 = 358,33 joule.